Analysis of Vark Learning Styles in Elementary School Students' Mathematical Concept Understanding - Hidayati, Vivi Rachmatul; Wahyuningsih, Baiq Yuni; Nurmawanti, Iva; Putri , Hikmah Ramdhani (Griya Journal of Mathematics Education and Application, 2025)
This study aims to identify elementary school students' understanding of mathematical concepts based on Neil D. Fleming's learning style theory (VARK), which consists of four main categories: Visual, Auditory, Read/Write, and Kinesthetic. A descriptive qualitative approach was used in this research, with the subjects being sixth-grade students of SDN 14 Cakranegara. The research instruments included learning style questionnaires, mathematical concept comprehension tests, and interviews. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The results showed that the majority of students had a kinesthetic learning style, indicating a preference for learning through physical activities and hands-on practice. Students with a kinesthetic learning style demonstrated a better understanding of mathematical concepts when learning methods involved physical activities. Additionally, several students exhibited a combination of visual, auditory, and read/write learning styles, reflecting variations in how they understand and apply mathematical concepts. Based on these findings, the study recommends that teachers implement varied teaching methods tailored to students' learning styles to enhance their understanding of mathematical concepts.